Dark Doctoring Types in Fiction and in Life - Hurwitz, Brian (Status Quaestionis, 2014)
The life of the UK general practitioner Dr Harold Shipman is one of the most important medico-moral tales of our time; not only because he was a serial killer who murdered fifteen patients and killed hundreds more; not only because his activities led directly to two public inquiries, a review of death certification and of the UK coronership, to irresistible demands for medical re-validation, and the fading of 150 years of medical self-regulation. Though Shipman’s motives remain obscure he accomplished something more significant than these bureaucratic changes, some of which were in train before his activities came to light. Shipman succeeded in adding to the actual and symbolic possibilities of modern family doctoring: to one end of the spectrum of possible characteristics, preoccupations and traits that could lie behind the professional persona of the doctor, Shipman added the appetites, drives and satisfactions of the serial killer. Yet Shipman was a most popular and hard-working GP, considered by his patients an excellent doctor. How was he mistaken for a good doctor and allowed to poison with impunity? This paper investigates fictional depictions of medical figures and health care organisations where beneficence as a moral principal is centrally distorted or turned upside down, throwing into relief the extent to which symbolic configurations of doctors are equated with good and trusted work.